A "3E" kritérium érvényesülése a felsőoktatási intézmények gazdálkodásában - Ágoston Anita (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2014)
The growing of the role of the state in many countries caused a big challenge. The situation became especially strained because the since 2008 extended fiscal crisis and the state budget consequences of this. The maintenance of the previous services; either the education, or the health care system we analyse; has led to the increase of the budget expenditures. The problem of higher education can be divided into two parts. On the one hand we can find financial problems, which stem from the decreasing public resources, on the other hand the lack of effective management cause wasting. To summarize on the institutional level the biggest problem is the efficient and effective use of the declining sources. The measurement of the performance is difficult. Our aim is to show why makes problem the using of the "3E" criterion, economy, efficiency, effectiveness in the management of the higher education institutions.